2021
DOI: 10.1155/2021/1738932
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiological Trends of Head and Neck Cancer: A Population-Based Study

Abstract: Background. Over the past decades, lots of advance have occurred in the prevention, diagnosis, and treatment of head and neck cancer (HNC). However, the contemporaneous incidence and survival trends, on the basis of population-based registry, have not been reported. Methods. The HNC cancer cases were accessed from the Surveillance, Epidemiology, and End Results (SEER) database. The incidence trend was analyzed by joinpoint analysis, with the survival trend being analyzed by period analysis of relative survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 52 publications
3
48
0
2
Order By: Relevance
“…Similarly, while Washington D.C. appears to be a high-density area, surgeons practicing there likely serve patients from Maryland and Virginia. Nebraska is the other state with the number of head and neck surgeons (11) in excess of the national average. Nebraska is neighboring two states (Wyoming and South Dakota), one with no head and neck surgeons and the other with a low number of practicing surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, while Washington D.C. appears to be a high-density area, surgeons practicing there likely serve patients from Maryland and Virginia. Nebraska is the other state with the number of head and neck surgeons (11) in excess of the national average. Nebraska is neighboring two states (Wyoming and South Dakota), one with no head and neck surgeons and the other with a low number of practicing surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the Surveillance, Epidemiology and End Results (SEER) database demonstrated that the incidence of head and neck cancer (excluding thyroid cancer) in the United States has fluctuated significantly over the past 20 years with a slight average annual percentage increase of 0.6%. 11 It is speculated that although traditional risk factors including tobacco and alcohol abuse have decreased among the population, stagnation in head and neck cancer rates may be attributable to widespread HPV prevalence. 12 Independent studies of thyroid cancer reveal that the incidence of thyroid cancer that was increasing for many years has been more steady in most recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) is the 6th most common type of cancer worldwide [1]. Of all head and neck cancers, approximately 30% originate from the larynx, resulting in 52000 newly diagnosed patients annually in Europe [2].…”
Section: Introductionmentioning
confidence: 99%
“…There were approximately 932,000 new HNC patients worldwide in 2020, of which 467,000 patients had died ( Sung et al, 2021 ). Although in the past 40 years, with the continuous developments in detection and treatment technologies, the 5-years survival rate of HNC has grown from 54.1% to 66.8%, but it still cannot meet the needs of patients for a more extended survival period ( Guo et al, 2021 ). The incidence of distant metastases from HNC ranges from 8.9–13.8%, and distant metastases is one of the main challenges that restrict the successful treatment of HNC patients ( Lee et al, 2012 ; Duprez et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%